It is all in the surv-eye: can eye tracking data shed light on the internal consistency in self-report questionnaires on cognitive processing strategies? - Margot Chauliac; Leen Catrysse; David Gijbels; Vincent Donche (EARLI, 2020)
Although self-report questionnaires are widely used, researchers debate whether responses to these types of questionnaires are valid representations of the respondent's actual thoughts and beliefs. In order to provide more insight into the quality of questionnaire data, we aimed to gain an understanding of the processes that impact the completion of self-report questionnaires. To this end, we explored the process of completing a questionnaire by monitoring the eye tracking data of 70 students in higher education. Specifically, we examined the relation between eye movement measurements and the level of internal consistency demonstrated in the responses to the questionnaire. The results indicated that respondents who look longer at an item do not necessarily have more consistent answering behaviour than respondents with shorter processing times. Our findings indicate that eye tracking serves as a promising tool to gain more insight into the process of completing self-report questionnaires.